The question of bumiputera participations in urban retail sector: Towards urban livability - Sulaiman, Siti Umira; Idrus, Shaharuddin; Hadi, Abdul Samad (2015)

(untitled)
Retail sector is one of the important components in urban economic activity for urban livability. Livability of the urban area contributes to the sustainability of urban retailing. Since retail sector is the lung of economy for urban areas, an in-depth study to understand the framework of this sector should be emphasized. This paper discusses the participation of Bumiputera in urban retail sector focusing on the Seremban Municipal Centre (SMC) as the designated study area. The purpose of this paper is to examine the role of the New Economic Policy (NEP) in bringing economic equity by ensuring 30 per cent of Bumiputera participation in urban retail sectors and to look into the pattern of Bumiputera consumers buying goods in SMC. Bumiputera participation in retail activity is still low as compared to the NEP target. While the NEP was established (in 1970), the targeted results are still unclear. To achieve sustainable quality of life from the economic perspective, local economic equilibrium plays an important role. Economic balance for every ethnic group should be emphasized in order to achieve economic equality and cohesion between ethnic groups. The results obtained through primary and secondary data indicated that Bumiputera retailers’ involvement constitutes only 7 per cent, while the remaining 93 per cent are from non Bumiputeras (Chinese 80 per cent and India 13 per cent). In addition, the trend for the past three decades shows a mere 6 per cent increase in Bumiputera participation in retail sector in SMC. Bumiputera retailers’ are involved in specific businesses such as restaurant, beauty care, travel and insurance agency, tuition centre, boutique and also private clinics. The result shows that Bumiputera participation in retail sector is still low and urban planners should play bigger roles to ensure Bumiputera’s retail activities are sustainable in the SMC. Based on consistent development of Bumiputera retailers over the past 33 years, we extrapolated that the quality of life of this group is sustainable and consistent as compared to other ethnic groups. 80 per cent of Bumiputera consumers tend to choose services while visiting this area. Therefore, it shows the relationship between Bumiputeras’ consumption pattern and the economic status for their retailers in SMC area. This consistency plays an important role in maintaining the culture, tradition and quality of life of the Bumiputera group, as far as availability of goods and services is concerned.